Resonant interferometric lithography beyond the diffraction limit - Kiffner, M; Evers, J; Zubairy, MS (2008)
A novel approach for the generation of subwavelength structures in interferometric optical lithography is described. Our scheme relies on the preparation of the system in a position dependent trapping state via phase shifted standing wave patterns. Since this process only comprises resonant atom-field interactions, a multiphoton absorption medium is not required. The contrast of the induced pattern does only depend on the ratios of the applied field strengths such that our method in principle works at very low laser intensities. © 2008 The American Physical Society.